Test Carbohydrate and Protein Content in Commercial Condensed Milk (SKM) Qualitative and Quantitative - Panjaitan, Riong Seulina; Christian, Yulius Evan; Wijaya, Bagas Eva; Andrian, Rahmat (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2023)
Sweetened condensed milk (SKM) is a milk product obtained by evaporating some of the water from pure milk with the addition of sugar. SKM is not a sterile product, but its preservation depends on the sugar content; (1) Background: Qualitative and quantitative tests of carbohydrates and proteins were carried out to determine the presence of carbohydrates and proteins in SKM. The qualitative test is based on a change in color or precipitate formed, while the quantitative test is to determine carbohydrate and protein levels; (2) Method: Qualitative and quantitative test of carbohydrates with the DNS method. Qualitative and quantitative test of protein with the Lowry method; (3) Results: Qualitative analysis of carbohydrates Molisch test on SKM